Generalizations of the normal basis theorem - Björkholdt, Elise; Lundström, Patrik (MATHEMATICA SCANDINAVICA, 2004)
We give several generalizations of the normal basis and primitive element theorems for a finite Galois field extension, with an infinite base field. These generalizations are obtained by considering polynomial expressions of conjugates of a fixed element.